TINGKAT KEPATUHAN PERAWAT DALAM PENERAPAN SURGICAL SAFETY CHEKLIST TIME OUT DI OPERATING THEATRE RUMAH SAKIT MURNI TEGUH MEDAN - Irma Jiliana Ripa Jaya Sinambela; Rostime Hermayerni Simanullang (Indonesian Trust Nursing Journal, 2023)
The mechanism for using the Surgical Safety Checklist is carried out for improvement by involving multiple professions (surgeons, anesthesiologists, anesthesiologists, and surgical nurses). Use of and adherence to surgical safety checklists results in reduced postmanipulation morbidity and mortality. While the benefits of using a surgical safety checklist resulted in a 47% reduction in mortality and 36% reduction in morbidity after habituation. The purpose of this study is to determine the level of adherence to the implementation of the Surgical Safety Checklist time out in the Operating Theater. The type of research used is descriptive quantitative. The population in this study were all nurses working in the operating room of Murni Teguh Hospital, Medan, consisting of 30 people. The instrument used is a questionnaire sheet. The result that majority of respondents aged 20-30 years were 21 people (70.0%) and a minority > 40 years were 1 person (3.3%), for the education of the majority of respondents with DIII education were 20 people (66.7%) and Minor education Nurses as many as 10 people (33.3%), and the characteristics of length of service the majority of nurses worked for < 3 years as many as 19 people (60.0%) and minorities worked > 3 years as many as 11 people (36,%). The conclusion is the level of adherence to the implementation of the Surgical Safety Checklist time out in the operating room of Murni Teguh Hospital, the majority of nurses obeyed as many as 27 people (90.0%) and the minority did not comply as many as 3 people (10.0%). For future researchers to conduct further research on the implementation of patient safety programs, especially the implementation of a safety checklist in the operating room, which is seen from various aspects that have not been reviewed in this study, such as the relationship between knowledge, motivation and compliance with the implementation of Surgical Safety Checklist Time Out. Abstrak Mekanisme penggunaan Surgical Safety Checklist dilakukan untuk perbaikan dengan melibatkan multi profesi (dokter bedah, dokter anestesi, penata anestesi, dan perawat bedah). Penggunaan dan kepatuhan terhadap checklist keselamatan bedah menghasilkan penurunan mortalitas dan morbiditas pasca pembedahan. Sedangkan manfaat Penggunaan checklist keselamatan bedah menghasilkan penurunan 47% mortalitas dan morbiditas berkurang 36% pasca pembedahan.Tujuan penelitian ini untuk mengetahui tingkat kepatuhan penerapan Surgical Safety Cheklist time out di Operating Theater. Jenis penelitian yang digunakan adalah deskriptif kuantitatif. Populasi dalam penelitian ini adalah seluruh perawat yang bekerja di ruang operating theater Rumah Sakit Murni Teguh Medan sebanyak 30 orang. Instrumen yang digunakan adalah lembaran kuesioner. Hasilnya adalah bahwa Umur responden mayoritas 20 - 30 tahun sebanyak 21 orang (70,0 %) dan minoritas umur > 40 tahun sebanyak 1 orang (3,3%), untuk pendidikan mayoritas responden berpendidikan DIII sebanyak 20 orang (66,7%) dan minoritas berpendidikan Ners sebanyak 10 orang (33,3%), dan karakteristik lama bekerja mayoritas perawat bekerja selama < 3 tahun sebanyak 19 orang (60,0%) dan minoritas bekerja > 3 tahun sebanyak 11 orang (36,%). Disimpulkan bahwa Tingkat kepatuhan penerapan Surgical Safety Cheklist time out di ruang operating theater RS Murni Teguh mayoritas perawat patuh sebanyak 27 orang (90,0%) dan minoritas tidak patuh sebanyak 3 orang (10,0%). Bagi peneliti selanjutnya untuk melakukan penelitian lebih lanjut tentang penerapan program patient safety terutama pelaksanaan cheklist keselamatan di kamar bedah yang di lihat dari berbagai aspek yang belum dikaji pada penelitian ini seperti hubungan antara pengetahuan, motivasi dengan kepatuhan.